ANALISIS PERKERASAN LANDAS PACU BANDAR UDARA HUSEIN SASTRANEGARA, BANDUNG - Ariel Winfried; Luky Surachman; Christina Sari (Jurnal Infrastruktur, 2019)
Husein Sastranegara Airport which can be located at the heart of Bandung city nowadays has a runway with its PCN classification fixed at 50 F/C/X/T or equals to a total flexible type pavement thickness precisely on 740 mm. Nevertheless, Boeing 737-800 defines its classification at maximum state up to 51 on ACN scale. Therefore, overlay act upon runway pavement needs to be studied in order to enhance its classification. ACN/PCN is one of ICAO renowned method to determine pavement thickness, while recently FAA has developed a cutting-edge method by using a computerized program called FAARFIELD (FAA Rigid Flexible Iterative Elastic Layer Design). In accordance with the earlier issues, ICAO method analyzes the need of 1041.4 mm pavement thickness for graphical technique and 940.6 mm for analytical technique, while FAARFIELD should only require 840.8 mm pavement thickness in determining its flexible type runway due to the previous overlay act. The presented results of both methods established that runway pavement of Husein Sastranegara Airport shall be improved by an overlay layer immediately